(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
In this article are contained the research of the mountain-valley serozem soils of Kyrgyzstan and their classification. By results of researches regularity of increase of the humus contenttypical serozem is traced that is connected with the change of conditions of soil formation caused by vertical zonality of distribution of soils which is confirmed as well by literary data where it is said that the main criterion for differentiation of above-mentioned soils is the degree of the humus content.